Rancang Bangun Aplikasi Business Intelligence Berbasiskan Arsitektur Aplikasi Akuntansi Accurate - Philbert Lukito Setiawan; Adi Suryaputra Paramita (Universitas Ciputra Surabaya, 2015)
Technological developments had an impact on all aspects including in business. There is a problem when technology can’t be regulated properly cause a negative impact, this called big data. The solution for this problem is business intelligence which providing additional value in the data. When BI implemented, businesses can perform an analysis of the business and can be used as a strategy formulation. On the other hand, the development of technology in the business world also began in Indonesia. One of the applications most used by user is accurate. Due to the target market of accurate application of general market, accurate doesn’t have some special features that are required by the company. The purpose of this research is expecte to create busineess accurate intelligence on an architecture that can provide additional value for the company. This research focuses on the design and manufacture of business intelligence applications query the data that converts data from the database accurate data is ready to be analyzed. Making an application using Visual Basic programming language and database firebird. The process of needs analysis was conducted by interview, application studies, comparative studies and database studies. Based on the analysis, accurate database is mapped into four major subjects, namely sales, purchase, inventory and the person who becomes the source of the data from business intelligence made. For the test, the research uses a database of real companies that have used accurate application. From the test results, can disumpulkan that the application has successfully made the analysis based on source data that has been created.